Metrizamide Sagittal Tomography: Adjunct to CT Cisternography of the Sellar Region - Davis, Kenneth R.; Zito, Joseph L.; Hesselink, John R.; Taveras, Juan M.; Kjellberg, Raymond N. (American Journal of Neuroradiology, 1980)
A total of 30 patients with pituitary adenoma was studied by sagittal polytomography en route to coronal and axial computed tomography (CT) cisternography after a low FDA-approved dose of 6 ml of 170 mg 1/ml metrizamide via lumbar injection. The requirement for defining the relation of the optic nerves and chiasm to the intrasellar contents or suprasellar mass before proton beam irradiation or certain surgical approaches was satisfied. Pneumoencephalography as a supplemental procedure to CT and CT cisternography was replaced. The concomitant elimination of conventional sellar polytomography and pneumoencephalography results in decreased total radiation exposure and a more comfortable, expeditious workup.